Hubungan Pelayanan Kesehatan dengan Kepuasan Pasien PBI (Penerimaan Bantuan Iuran) Rawat Inap di Puskesmas Marawola: Hubungan Pelayanan Kesehatan dengan Kepuasan Pasien PBI (Penerimaan Bantuan Iuran) Rawat Inap di Puskesmas Marawola - Benny H.L Situmorang; Nuriany Nuriany; Tigor H Situmorang; Hasnidar Hasnidar (Neolectura, 2022)
PBI member is poor people and unable people to join in Health Insurance Programme. Based on observation of researcher in marawola PHC that health services have not been maxmimal providing by poor satisfaction of patients explanation. It influenced by some factors such as in a rush assesment of doctor in ward, so patients have no chance to consult their disease, limited drugs administering, referral patient system that take time and complicated and if patient wants to referred to hospital, it only refer to Torabelo General Hospital, Sigi Regency. So, this research aim to observe the correlation of health services toward satisfaction of in patient PBI. Population number was 75 patients, but only 47 respondents that it taken by purposive sampling technique. Instruments used was questionnaire and data analyzed by chi-square test with significant level (? = 0,05). Result found that p-value 0,008, it shown that having correlation of health services toward in patient PBI satisfaction in marawola PHC. Suggestion, that nurses emphaty and drugs administering should be improved for supporting the health quality of services for patient’s satisfaction toward health services that givent.